2020
DOI: 10.31235/osf.io/tjvgy
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Potential to Infer the Historical Pattern of Cultural Macroevolution

Abstract: Phylogenetic analyses increasingly take centre-stage in our understanding of the processes shaping patterns of cultural diversity, and cultural evolution over time. Just as biologists explain the origins and maintenance of trait differences among organisms using phylogenetic methods, so anthropologists studying cultural macroevolutionary processes use phylogenetic methods to uncover the history of human populations and the dynamics of culturally transmitted traits. In this paper we revisit concerns with the va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 51 publications
(79 reference statements)
0
4
0
Order By: Relevance
“…In principle, archaeological and paleoclimatic data could be incorporated into future analyses as ancestral states and exogenous variables, respectively (69). One concern in all phylogenetic studies of cultural evolution is that horizontal transmission between societies means that trait evolution is not strictly tree-like (vertical) (70,71). In principle, horizontal transmission should not bias our results: we estimated how changes in RI affect TSD, which does not depend on the mechanism of cultural change being vertical.…”
Section: Discussionmentioning
confidence: 99%
“…In principle, archaeological and paleoclimatic data could be incorporated into future analyses as ancestral states and exogenous variables, respectively (69). One concern in all phylogenetic studies of cultural evolution is that horizontal transmission between societies means that trait evolution is not strictly tree-like (vertical) (70,71). In principle, horizontal transmission should not bias our results: we estimated how changes in RI affect TSD, which does not depend on the mechanism of cultural change being vertical.…”
Section: Discussionmentioning
confidence: 99%
“…The necessity to consider phylogenetic context when analyzing interspecies data has been widely adopted in many fields of biology, including ecology (e.g., Wu et al, 2021), animal behavior (e.g., Balasubramaniam et al, 2012), anthropology (e.g., Lukas, Towner and Borgerhoff Mulder, 2021) and conservation science (e.g., Fritz and Purvis, 2010). In contrast, in other sub-disciplines of biology, especially those which study phenomena at the cell or molecular level, phylogenetic statistical practices are less commonplace.…”
Section: Introductionmentioning
confidence: 99%
“…One way to get around these problems is to use the methods of phylogenetic analysis developed in evolutionary biology (T. E. Currie & Mace, 2012;Mace & Holden, 2005;Watts et al, 2015). However, this approach can be highly sensitive to assumptions underlying the phylogenetic analysis (Lukas et al 2021), as demonstrated by efforts to reconstruct the origins of the Indo-European linguistic family (Bouckaert et al, 2012) and the debates these have prompted (Anthony & Ringe, 2015;Chang et al, 2015;Pereltsvaig & Lewis, 2015).…”
Section: Introductionmentioning
confidence: 99%